Four new Neotropical species of Stilobezzia (Acanthohelea) Kieffer (Diptera: Ceratopogonidae) - Cazorla, Carla G.; Spinelli, Gustavo R. (Zootaxa, 2010)
The subgenus Stilobezzia (Acanthohelea) Kieffer is newly recorded from several provinces of northern Argentina and Paraguay, and the following four new species are described, and illustrated: S. (A.) guarani, S. (A.) monopicta, S. (A.) paranaense and S. (A.) xerophila. These species are compared with similar congeners.